Thermal comfort along the marathon course of the 2020 Tokyo Olympics - Honjo, T.; Seo, Y.; Yamasaki, Y.; Tsunematsu, N.; Yokoyama, H.; Yamato, H.; Mikami, T. (International Journal of Biometeorology, 2018)
The Olympic Games will be held in Tokyo in 2020 and the period will be the hottest period of the year in Japan. Marathon is a sport with a large heat load, and it is said that the risk of heat stroke rises more than other sports activities. The thermal environment of the 2020 Tokyo Olympic marathon course is analyzed by using wet-bulb globe temperature (WBGT) and Universal Thermal Climate Index (UTCI) map of the center area of Tokyo. The change due to the place, the effect of the shadow of the building, and the position on the course was analyzed from the distribution of WBGT and UTCI in the short-term analysis of sunny day from August 2 to August 6, 2014. To make the distribution map, we calculated distributions of sky view factor and mean radiant temperature of the 10 km × 7.5 km analyzed area in the center of Tokyo. Distributions of air temperature and humidity are calculated from Metropolitan Environmental Temperature and Rainfall Observation System data, which is a high-resolution measurement network. It was possible to incorporate the local variation of temperature and humidity of the analyzed area. In the result, the WBGT is about 1 °C lower and the UTCI is about 4-8 °C lower in the shadow of buildings from 9:00 to 10:00 than in the sunny side. As a cooling method, making a shadow is a relatively effective method. The variation along the course considering the distribution of meteorological data within the area is about 0.5 °C WBGT and 1 °C UTCI range. If we allow the error of this range, one-point meteorological data can be applied for the estimation along the course. Passing the right side (left side in the case of return) of the course could keep the accumulated value slightly lower along the course in the morning because the marathon course roughly runs from west to east and buildings` shadow is on the relatively right side (south side). But practically, the effect of changing the position on the course was small. The long-term analysis on the degree of risk for each hour was also carried out by using one-point data of the first 10 days of August from 2007 to 2016. The risk increased rapidly after 8:00. It will be safer if the marathon race is finished before 9:00 or if the race is held after 19:00.